Metallophilic Interaction-Mediated Hierarchical Assembly and Temporal-Controlled Dynamic Chirality Inversion of Metal–Organic Supramolecular Polymers - Yao, Longfei; Fu, Kuo; Wang, Xuejuan; He, Menglu; Zhang, Wannian; Liu, Peng-Yu; He, Yu-Peng; Liu, Guofeng (ACS nano, 2023)
The study of dynamic supramolecular chirality inversion (SMCI) not only helps to deepen the understanding of chiral transfer and amplification in both living organizations and artificially chemical self-assembly systems but also is useful for the development of smart chiral nanomaterials. However, it is still challenging to achieve the dynamic SMCI of the self-aggregation of metal–organic supramolecular polymers with great potential in asymmetric synthesis, chiroptical switches, and circular polarized luminescence. Here, we successfully developed a hierarchical coassembly system based on the mPAzPCC and various metal ions with effective chirality transfer and temporal-controlled SMCI. Due to the dynamic self-assembly and hierarchical chirality transfer of the Ag+/mPAzPCC complex driven by metallophilic interaction and coordination, morphological transition with nanoribbons, helical nanoribbons, and chiral nanotubules was successively obtained. Interestingly, the SMCI of chiral nanoaggregates was precisely regulated by solvents and metal ions in the Cu2+/mPAzPCC and Mn2+/mPAzPCC system. Besides, temporal-controlled dynamic SMCI switching from helix to bundled helix was clearly revealed in the aggregation of Cu2+/mPAzPCC, Mn2+/mPAzPCC, and Bi3+/mPAzPCC systems. This work provides a metallophilic interaction-mediated helical assembly pathway to dynamically modulate the chirality of metal–organic complex-based assemblies and deepen the understanding of the hierarchically dynamic self-assembly process, which would be of great potential in metal ion-mediated supramolecular asymmetric catalysis and bioinspired chiral sensing.